A Case of mistaken identity: Rhabdomyosarcoma development from endothelial progenitor cells. (4th July 2018) - Drummond, Catherine J.; Hatley, Mark E.
ABSTRACT: Rhabdomyosarcoma (RMS) histologically resembles developing skeletal muscle and is thought to solely originate from a differentiation block in muscle progenitors. We demonstrate that RMS can arise from endothelial progenitor cells following reprogramming and myogenic transdifferentiation. These results highlight how tumors with identical morphological features can arise from different cell types and offer insight into RMS formation in non-myogenic tissue.